Infection Prevention and Control Education for Environmental Services Workers (ESW): "Cleaner is Safer – ESW on the Front-line of Infection Prevention". (4th October 2017) - Martin, Elena; Salsgiver, Elizabeth; Simon, Matthew S; Greendyke, William; Gramstad, James; Tejeda, Angel; Weeks, Roy; Woodward, Timothy; Saiman, Lisa; Furuya, E Yoko; Calfee, David P
Abstract: Background: Studies suggest that improving environmental cleaning and disinfection reduces pathogen transmission and prevents healthcare-associated infections (HAIs). We designed and administered an educational program for hospital ESW based on findings from a 2015 knowledge, attitudes, and practices survey. Methods: An interactive 5-part educational program was given to front-line ESW at 5 acute care hospitals from 7/16 to 3/17 using principles of adult learning theory. Audience response system (ARS), videos, demonstrations, role-playing, and graphics were used to illustrate concepts and emphasize the rationale for HAI prevention strategies. Topics included HAIs, hand hygiene, isolation precautions, personal protective equipment, daily and discharge cleaning, and strategies to overcome common challenges and barriers. Evaluation included ARS questions, written evaluations, and assessment of daily cleaning before and after education using the 3M™ Clean-Trace™ Hygiene Management System. Clean surfaces were those with <250 relative light units detected. Chi-square tests were performed, where appropriate. Results: On average, 357 (range: 303-391) ESW attended each of the 5 program components. Most participants rated the presentations as 'excellent' or 'very good' (93%) and agreed they were useful (95%). After the program, participants indicated they were more comfortable donning/doffing PPE (91%), performing hand hygiene (96%), and better understood the importance of disinfecting high-touch surfaces (96%). The frequency of effective cleaning of high-touch surfaces in occupied patient rooms significantly improved following education (Table). Conclusion: A novel educational program, designed using adult learning theory, that addressed ESW's self-identified challenges was well-received and appears to have resulted in learning, behavior change, and improved daily cleaning. Future research will assess program sustainability and long-term impact on hospital cleanliness and patient outcomes. Disclosures: All authors: No reported disclosures.